Penerapan Model Pembelajaran Contextual Teaching Learning Dalam Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Ipa Kelas V SD Kristen 3 Bangunan Wuwuk - Rodaya, Nanda D; Mangantes, Meisie L.; Tuerah, Roos M. S. (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research was conducted in class V of SD Kristen 3 Gedung Wuwuk with the aim of improving student learning outcomes in science learning by using a contextual learning model (Contextual Teaching Learning). The research method used is Classroom Action Research (PTK) which consists of planning, implementation, observation and reflection. This activity was carried out in two meetings in two cycles. The subjects of this PTK were 11 class V students at SD Kristen 3 Gedung Wuwuk, consisting of 8 male students and 3 female students. The data collection technique for this research is seen from the observations and tests carried out. The observations carried out were based on observation instruments, while the tests carried out provided several questions or questions. In cycle I the learning outcomes obtained by students reached 53.18% and of the 11 students only 4 were successful, the other 7 students did not understand the material well and were declared unsuccessful. Therefore, the research continues in cycle II in order to achieve science learning outcomes by using the contextual learning model (Contextual Teaching Learning) optimally. In cycle II, student learning outcomes experienced a very significant increase, reaching 84.55%. From this percentage it can be said to be successful. Based on the results of this research, the conclusion is drawn that, the application of the Contextual Teaching Learning Model can improve science learning outcomes regarding Changes in Form of Objects in class V of Christian Elementary School 3 Gedung Wuwuk